Botany in the classroom: diagnosis of practical activities by elementary school teachers (Research, Society and Development, 2022)
Botany teaching traditionally presents great difficulties throughout the entire teaching-learning process. One of the barriers commonly faced by teachers is the design and implementation of practical activities. This study aimed to examine practical activities in school and the use of plants in classes, and which challenges teachers encounter to carry out this task in science education and botany teaching. Our methodology was based in the application of a qualitative questionnaire followed by theanalysis and interpretation of the questions. The survey was conducted in six public schools of Seropedica Municipality (Rio de Janeiro State, Brazil) participants of The Institutional Scholarship Program for Teaching Initiation (Programa Institucional de Bolsas de Iniciação à Docência - PIBID), in the Biology subproject from Universidade Federal Rural do Rio de Janeiro. Nineteen science teachers from basic education were interviewed. The results showed that although teachers recognize the importance of practical activities, most of them rarely implement such practices during classes. Difficulties are related to curriculum contents, adequate spaces for conducting practical classes, plant materials, classroom management, lack of assistants and bureaucracy. It was also observed that the use Angiosperms during practical activities prevailed. Thus, the purpose of the work was to verify the use of plants in practical activities and to assist with proposals for the elaboration of the same.